2019
DOI: 10.24263/2304-974x-2019-8-4-15
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spirulina platensis on the crumb firming of wheat bread during storage

Abstract: Introduction. The effect of Spirulina platensis on the crumb firmness during storage (96 h) of wheat bread was studied by measuring the deformation properties (total, plastic and elastic deformation). Materials and methods. Bread is obtained from wheat flour with the addition of Spirulina platensis (powder) in the amount of 2 or 4% by the weight of flour. The deformation properties of the bread crumb were studied 3, 24, 48, 72 and 96 hours after the baking. The deformation characteristics of the bread crumb ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…The reduced elasticity could be attributed to the nongluten flour composition and the specific fermentation capacity of the tested strains. Other studies on the rheological properties of gluten-free sourdoughs prepared with lactic acid bacteria also found that the addition of sourdough reduced the elasticity of the dough and improved the dough strength [ 69 , 96 , 97 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reduced elasticity could be attributed to the nongluten flour composition and the specific fermentation capacity of the tested strains. Other studies on the rheological properties of gluten-free sourdoughs prepared with lactic acid bacteria also found that the addition of sourdough reduced the elasticity of the dough and improved the dough strength [ 69 , 96 , 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…Bake loss (%) was determined following weighing each loaf before and after baking [ 67 ]. The bread loaves were wrapped in plastic bags and stored at room temperature (27 ± 2 °C) to determine the storage time (in days) until mold growth became visible [ 68 , 69 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The deformation properties (total, plastic and elastic deformation) of croissants crumb were studied at 3, 24, 48 and 72 h after baking. Total, elastic, and plastic deformation (D p ), presented in penetrometric units (PU), were measured by an automatic penetrometer (Zlateva and Chochkov, 2019). A 4-mm thick sample was cut from croissant and placed on flat surface of the lifting table of the device, which was raised until the upper surface of the sample lightly touched the lower end of the immersion body.…”
Section: Croissants Analysesmentioning
confidence: 99%